2011
DOI: 10.5588/ijtld.10.0438
|View full text |Cite
|
Sign up to set email alerts
|

Cash transfer and microfinance interventions for tuberculosis control: review of the impact evidence and policy implications

Abstract: OBJECTIVE To quantify the impact of cash transfer and microfinance interventions on a selected list of tuberculosis (TB) risk factors and assess their potential role in supporting TB control. DATA SOURCE Published and unpublished references identified from clinical and social electronic databases, grey literature and web sites. METHODS Eligible interventions had to be conducted in middle- or low-income countries and document an impact evaluation on any of the following outcomes: 1) TB or other respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 40 publications
1
88
0
3
Order By: Relevance
“…Although information on impact of economic strengthening on uptake of HIV care services is lacking, improved uptake of HIV screening and treatment and improved treatment outcomes have been reported in some social protection interventions, such as cash transfers (Boccia et al 2011). In Uganda, studies on economic empowerment for adolescents showed that Basset building^reduced poverty, improved psychosocial functioning, and positively impacted attitudes and behaviors (Ssewamala et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Although information on impact of economic strengthening on uptake of HIV care services is lacking, improved uptake of HIV screening and treatment and improved treatment outcomes have been reported in some social protection interventions, such as cash transfers (Boccia et al 2011). In Uganda, studies on economic empowerment for adolescents showed that Basset building^reduced poverty, improved psychosocial functioning, and positively impacted attitudes and behaviors (Ssewamala et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…A positive impact on household food security was documented in respectively eight of nine and three of five cash transfer and microfinance interventions. Improved health care access was documented respectively in 10 of 12 cash transfer and four of five microfinance interventions [43]. No study, however, analysed the cost effectiveness in detail.…”
Section: Discussionmentioning
confidence: 99%
“…61 However, there was little operational evidence to guide implementation or evaluate the impact of TBrelated socio-economic support, including cash transfer interventions. 9,15,17,18 , 54-56 , 62-68 Building on the lessons learnt during the ISIAT project, 15 extensive expert and TB civil society consultation, 54 a systematic review of cash transfer interventions 55 and the phase 1 published research, 11 our IFHAD research group was funded by the Joint Global Health Trials (a consortium of Wellcome Trust, Medical Research Council and the UK Department for International Development) to undertake the Community Randomized Evaluation of a Socio-economic Intervention to Prevent TB (CRESIPT) project. The conception, design, and implementation of the complex TB-specific socio-economic intervention is described in more detail elsewhere.…”
Section: S83mentioning
confidence: 99%